Approach to Eosinophilia Presenting With Pulmonary Symptoms - Rosenberg, Chen E. (Chest, 2021)
Eosinophilia with pulmonary involvement is characterized by the presence of peripheral blood eosinophilia, typically ≥500 cells/mm(3), by pulmonary symptoms and physical examination findings that are nonspecific, and by radiographic evidence of pulmonary disease and is further supported by histopathologic evidence of tissue eosinophilia in a lung or pleura biopsy specimen and/or increased eosinophils in BAL fluid, usually >10%. Considering that there are a variety of underlying causes of eosinophilia with pulmonary manifestations and overlapping clinical, laboratory, and radiologic features, it is essential to approach the evaluation of eosinophilia with pulmonary findings systematically. In this review, we will describe a case presentation and discuss the differential diagnosis, a directed approach to the diagnostic evaluation and supporting literature, the current treatment strategies for pulmonary eosinophilia syndromes, and the levels of evidence underlying the recommendations, where available. Overall, optimal management of eosinophilic lung disease presentations are directed at the underlying cause when identifiable, and the urgency of treatment may be guided by the presence of severe end-organ involvement or life-threatening complications. When an underlying cause is not easily attributable, management of eosinophilia with pulmonary involvement largely relies on eosinophil-directed interventions, for which biologic therapies are increasingly being used.